Tree-Growth Variations of Nothofagus antarctica Related to Climate and Land Use Changes in Southern Patagonia, Argentina - Vettese, Evangelina Soledad; Villalba, Ricardo; Orellana Ibáñez, Ivonne Alejandra; Peri, Pablo Luis (Springer Nature, 2021)
Isolated forest patches of Nothofagus antarctica (ñire) are frequent in the Patagonian forest-steppe ecotone. These remnants, also called relicts (R), are separate from the continuous forests (C). Over the past century, these ecotonal forests have been impacted by anthropogenic activities, including fires, logging, and cattle ranching. In order to identify in N. antarctica ring-width records the variations in tree growth associated with documented changes in land use, five sites were selected in Santa Cruz, Argentina. In each site, increment cores from R and C were collected. We developed individual chronologies, and the relationships between regional climate variations and N. antarctica growth were established for each forest type and site. The similarities/differences between site-paired chronologies (R-C) were estimated by calculating moving correlation coefficients lagged by 1 year. N. antarctica regional growth was directly related to precipitation during the current growing season (November–December; r = 0.34, n = 62, p < 0.01), and inversely related to temperature (December–March; r = −0.58, n = 62, p < 0.001). Since the middle of the twentieth century, a progressive decrease has been recorded in regional radial growth, consistent with an increase in summer temperature and a decrease in spring precipitation. In the context of this regional response of N. antarctica to climate, differences in growth patterns between R and C were associated with past changes in land use. Overall, the largest differences between R and C chronologies were concurrent with the settlement of cattle ranches and the associated use of forests. Conversely, similarities between R and C records increased after the establishment of protected areas and during the implementation of similar management practices in both forest types. Our research provides the first dendrochronological records from Nothofagus antarctica for the Argentinean Patagonia and represents one of the first efforts to identify in tree-rings past changes in livestock practices in southern South America.